Peranan Gaya Kepemimpinan terhadap Keterlibatan Generasi Milenial dalam Pelayanan di Jemaat Kristen Indonesia Mahanaim Blitar - Efie Linda Kundjarijati; Fibry Jati Nugroho (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Leadership style is the leader's way of influencing the group so that they can work together to achieve the goals that have been set. The millennial generation or what is known as generation Y is a social community whose main characteristics are being literate and familiar with technology. The aim of the research is to determine the leadership style of the pastor and its role in the involvement of the millennial generation in ministry at the JKI Mahanaim Blitar church. This research uses a qualitative approach with a descriptive type of research which aims to find out and describe the role of leadership style on the involvement of the millennial generation in service. Meanwhile, the data collection techniques used in this research are primary data and secondary data obtained through observation, interviews and documentation with pastors, congregation boards, and millennial congregation members. The results of the research concluded that the leadership style of the pastor in leading congregation members at JKI Mahanim Blitar tends to lead to democratic, autocratic and situational leadership styles. This is seen from various aspects, including the pastor's ability to solve problems, the policies taken, and the ability to communicate. The impact of the pastor's leadership style is that the number of millennial congregations involved in ministry increases every year, they have high commitment and loyalty and cadre formation in every field of service is going well.